A New Code-Based Traceable Ring Signature Scheme. (29th April 2022) - Qi, Yanhong; Wang, Li-Ping
Abstract : Traceable ring signatures (TRS) can reveal the identity of the signer if he signs two different messages on the same tag in the group of users. They are widely used in e-voting and cryptocurrencies such as Monero. However, there is still no secure code-based TRS scheme in the random oracle model (ROM). In this paper, we propose a code-based TRS scheme whose security is based on the hardness of the syndrome decoding problem and 2-regular null syndrome decoding problem. We show that our scheme is secure in the ROM in terms of tag-linkability, anonymity, and culpability. The signature size of our scheme is logarithmic in terms of the ring size.